High-Order Adaptive Dissipation Scheme Based on Vortex Recognition for Compressible Turbulence Flow (Communications in Computational Physics, 2024)
In the numerical simulation of compressible turbulence involving shockwaves, accurately capturing the intricate vortex structures and robustly computingthe shock wave are imperative. Employing a high-order scheme with adaptive dissipation characteristics proves to be an efficient approach in distinguishing small-scalevortex structures with precision while capturing discontinuities. However, differentiating between small-scale vortex structures and discontinuities during calculations hasbeen a key challenge. This paper introduces a high-order adaptive dissipation central-upwind weighted compact nonlinear scheme based on vortex recognition (named asWCNS-CU-Ω), that is capable of physically distinguishing shock waves and small-scale vortex structures in the high wave number region by identifying vortices withinthe flow field, thereby enabling adaptive control of numerical dissipation for interpolation schemes. A variety of cases involving Euler, N-S even RANS equations are testedto verify the performance of the WCNS-CU-Ω scheme. It was found that this newscheme exhibits excellent small-scale resolution and robustness in capturing shockwaves. As a result, it can be applied more broadly to numerical simulations of compressible turbulence.
Keywords: Weighted compact nonlinear scheme; high-order; shock-capturing; compressible turbulence.